Performance art in the public school: study about subversion in the school 1environment (Revista de Ensino em Artes, Moda e Design, 2020)
This text presents theoretical, methodological and practical notes on performan- ce-specific scenic constructions, elaborated through aesthetic-sensorial experiences, their reports and repercussions in the interior of public schools located in the interior of a periphery of the South Zone of the city of São Paulo-SP. It also contemplates dia- logue between artists, including in training, school and local communities, teachers, students and society. To view an art of performance as language and to consider her like transgressive tendence, the intention is to discuss the meanings of subversion, in the literal and simple sense, in a metalinguistic form, and as a component of school performance education environment.
Keywords: performace; subversion; public school